CD209 genetic polymorphism and tuberculosis disease. - Fredrik O Vannberg; Stephen J Chapman; Chiea C Khor; Kerrie Tosh; Sian Floyd; Dolly Jackson-Sillah; Amelia Crampin; Lifted Sichali; Boubacar Bah; Per Gustafson; Peter Aaby; Keith P W J McAdam; et al. (PLoS ONE)
Background Tuberculosis causes significant morbidity and mortality worldwide, especially in sub-Saharan Africa. DC-SIGN, encoded by CD209, is a receptor capable of binding and internalizing Mycobacterium tuberculosis. Previous studies have reported that the CD209 promoter single nucleotide polymorphism (SNP)-336A/G exerts an effect on CD209 expression and is associated with human susceptibility to dengue, HIV-1 and tuberculosis in humans. The present study investigates the role of the CD209 -336A/G variant in susceptibility to tuberculosis in a large sample of individuals from sub-Saharan Africa. Methods and findings A total of 2,176 individuals enrolled in tuberculosis case-control studies from four sub-Saharan Africa countries were genotyped for the CD209 -336A/G SNP (rs4804803). Significant overall protection against pulmonary tuberculosis was observed with the -336G allele when the study groups were combined (n = 914 controls vs. 1262 cases, Mantel-Haenszel 2 x 2 chi(2) = 7.47, P = 0.006, odds ratio = 0.86, 95%CI 0.77-0.96). In addition, the patients with -336GG were associated with a decreased risk of cavitory tuberculosis, a severe form of tuberculosis disease (n = 557, Pearson's 2x2 chi(2) = 17.34, P = 0.00003, odds ratio = 0.42, 95%CI 0.27-0.65). This direction of association is opposite to a previously observed result in a smaller study of susceptibility to tuberculosis in a South African Coloured population, but entirely in keeping with the previously observed protective effect of the -336G allele. Conclusion This study finds that the CD209 -336G variant allele is associated with significant protection against tuberculosis in individuals from sub-Saharan Africa and, furthermore, cases with -336GG were significantly less likely to develop tuberculosis-induced lung cavitation. Previous in vitro work demonstrated that the promoter variant -336G allele causes down-regulation of CD209 mRNA expression. Our present work suggests that decreased levels of the DC-SIGN receptor may therefore be protective against both clinical tuberculosis in general and cavitory tuberculosis disease in particular. This is consistent with evidence that Mycobacteria can utilize DC-SIGN binding to suppress the protective pro-inflammatory immune response.